Mortality causes in goldsmiths of Bangladesh: Findings from verbal autopsy (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Information on the mortality causes of goldsmiths in Bangladesh is limited. This study aimed to find out the mortality causes in a selected group of goldsmiths.Methods: A World Health Organization recommended questionnaire was adapted to conduct verbal autopsy of 20 deceased goldsmiths. Death-related information was gathered from the family members present during deceased’s illness preceding death. The mortality causes were determined by the interview outcomes and medical records-review.Results: The mean age of the goldsmiths at death was 59.2± 9.3 years. Among then, 70.0% were smokers and 50.0% were alcohol consumers. Cardiovascular diseases (CVD) were the most common immediate and underlying cause of death (60.0% and 45.0%, respectively).Conclusion: The life expectancy of goldsmiths was much lower than the average life expectancy of Bangladeshi population, where CVD was the primary cause of death. Smoking and alcohol consumption were prevalent among them. Awareness about healthy lifestyles should be prioritized for highly CVD prevention among the goldsmiths.